Nuclear magnetic resonance spectroscopy based metabolomics to identify novel biomarkers of alcohol-dependence - Mostafa, Hamza; M. Amin, Arwa; Arif, Nor Hayati; Murugaiyah, Vikneswaran; Ibrahim, Baharudin (Prince of Songkla University, 2017)
Alcohol misuse is a ravaging public health and social problem. Its harm can affect the drinkers and the whole society. Alcohol-dependence is a phase of alcohol misuse in which the drinker consumes excessive amounts of alcohol and has a continuous urge to consume alcohol. Current methods of alcohol dependence diagnoses are questionnaires and some biomarkers. However, both methods lack specificity and sensitivity. Metabolomics is a scientific field which deals with the identification and the quantification of the metabolites present in the metabolome using spectroscopic techniques such as nuclear magnetic resonance (NMR). Metabolomics helps to indicate the perturbation in the levels of metabolites in cells and tissues due to diseases or ingestion of any substances. NMR is one of the most widely used spectroscopic techniques in metabolomics because of its reproducibility and speed. Some recent metabolomics studies were conducted on alcohol consumption and alcohol misuse in animals and humans. However, few focused on identifying alcohol dependence novel biomarkers. A sensitive and specific technique such as NMR based metabolomics applied to find novel biomarkers in plasma and urine can be useful to diagnose alcohol-dependence.